PARTICIPACION DE Diplopia sp. EN EL ESCALDADO DEL ALCORNOQUE - Oliva i Estanyol, M; Molinas de Ferrer, M L (Scientia gerundensis, 1986)
This paper describes the association of Diplodia sp., a Sphaeropsidal fungus, with a new form of (<escaldat)) (dieback associated with trunk lessions) that we call <xancre secu (dry canker) in the cork-oak, Quercus suber L. The dry canker is a complex syndrome consisting of wilting and trunk canker lessions. The disease occurs in an acute form and then the tree dies quickly after cork removal; or it can follow an insidious form and the tree can react and form several layers of cork before dying. A description of the simptomatology is given. The fungus Diplodia sp. is isolated from diseased trees and it has infectious capatity on the living tissues. The isolate has conidial characteristics that slightly differ from other Diplodia parasitic in Quercus. Because the taxonomic revision of the genus is lacking we have not given an species name. The relation between ecological stress and disease is emphasized and some possible preventive measures are given.
Keywords: canker; cork-oak; forest pathology; Quercus suber L.; wilt